Existence results for a class of impulsive neutral fractional stochastic integro-differential systems with state dependent delay. Issue 5 (3rd September 2019) - Chaudhary, Renu; Pandey, Dwijendra N.
Abstract: In this paper, we provide a framework for study the mild solution to fractional neutral stochastic integro-differential systems with state dependent delay and noninstantaneous impulses in Hilbert spaces. To obtain the existence results, we have utilized the concepts of fractional calculus, fixed point theorems, stochastic analysis and semigroup theory. Finally, examples are provided to demonstrate the obtained results.